Fermented Sipjeondaebo-tang Alleviates Memory Deficits and Loss of Hippocampal Neurogenesis in Scopolamine-induced Amnesia in Mice - Park, Hee Ra (Sci Rep, 2016)
We investigated the anti-amnesic effects of SJ and fermented SJ (FSJ) on scopolamine (SCO)-induced amnesia mouse model. Mice were orally co-treated with SJ or FSJ (125, 250, and 500 mg/kg) and SCO (1 mg/kg), which was injected intraperitoneally for 14 days. SCO decreased the step-through latency and prolonged latency time to find the hidden platform in the passive avoidance test and Morris water maze test, respectively, and both SCO effects were ameliorated by FSJ treatment. FSJ was discovered to promote hippocampal neurogenesis during SCO treatment by increasing proliferation and survival of BrdU-positive cells, immature/mature neurons. In the hippocampus of SCO, oxidative stress and the activity of acetylcholinesterase were elevated, whereas the levels of acetylcholine and choline acetyltransferase were diminished; however, all of these alterations were attenuated by FSJ-treatment. The alterations in brain-derived neurotrophic factor, phosphorylated cAMP response element-binding protein, and phosphorylated Akt that occurred following SCO treatment were protected by FSJ administration. Therefore, our findings are the first to suggest that FSJ may be a promising therapeutic drug for the treatment of amnesia and aging-related or neurodegenerative disease-related memory impairment. Furthermore, the molecular mechanism by which FSJ exerts its effects may involve modulation of the cholinergic system and BDNF/CREB/Akt pathway.